INFLUENCE OF LEADERSHIP STYLE ON PERFORMANCE: A BIBLIOMETRIC REVIEW - Adrianza Putra; Renaldi Renaldi (Program Studi Administrasi Bisnis, Fakultas Komunikasi dan Bisnis, Universitas Telkom, 2023)
Leadership style is an external component that has a considerable influence on staff performance motivation. A good leadership style may enhance employee motivation and performance, whereas a negative leadership style can decrease employee motivation and performance. As a result, it is critical for organisations to understand and research successful leadership styles in order to increase employee engagement. In terms of bibliometric analysis, this article will analyse the link between leadership style and staff performance motivation. This essay will start by defining a leader, employee performance motivation, and leadership style.